Effect of macromicroelement complexes on productivity and photosynthetic activity of anthocyanin-containing potato varieties - Pavlov Maxim N.; Kulagina Polina V.; Khomyakova Karina N. (BIO Web of Conferences)
In the conditions of the Central Non-Chernozem region of Russia, the productivity and photosynthetic activity of anthocyanin- containing potato varieties Surpriz, Severnoye siyanie. and Amethyst were studied for various applications of macromicroelement complexes: the formulation of 2020 against the background of N120P140K180 and calculated on the basis of indicators of the removal of nutrients for yields of 30 and 40 t/ha (100% before planting, 99.5% before planting + 0.5% in foliar top dressing; 99% before planting + 1 % in foliar top dressing). The highest yield of tubers (36.4 t/ha) was obtained from the Surpriz variety, which had a higher yield than the Severnoye siyanie and Amethyst varieties by 4.8-5.9 t/ha, which ensures a higher net photosynthetic productivity (NPP) compared to other varieties by 0.9-1.1 g/m2 day. For all varieties, the most effective was the use of MMC 2020 against the NPP background, which provided an increase in different varieties from 9.0 to 14.4 t/ha due to the growth of the leaf surface (leaf area and PP), as well as the content of photosynthetic pigments in the leaves (CCI index). MMC can also be selected as optimal for all varieties in a dose calculated for approximately 30 t/ha of tubers in a variant combining 99.5% of the weight of the elements before planting and 0.5% in non-root top dressing. At the same time, all varieties have achieved the planned yield level, and the Severnoye siyanie variety has the maximum increase in control (7.6 t/ha), which is ensured by an increase in the NPP by 0.47-1.50 g/m2 per day and the CCI index during the maximum period for Surpriz and Severnoye siyanie varieties by 1.67-1.73 units.